2021
DOI: 10.3390/polym13152524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibre Orientation on Novel Continuous 3D-Printed Fibre-Reinforced Composites

Abstract: Among the several additive manufacturing techniques, fused filament fabrication (FFF) is a 3D printing technique that is fast, handy, and low cost, used to produce complex-shaped parts easily and quickly. FFF adds material layer by layer, saving energy, costs, raw material costs, and waste. Nevertheless, the mechanical properties of the thermoplastic materials involved are low compared to traditional engineering materials. This paper deals with the manufacturing of composite material laminates obtained by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The agglomeration of silica dioxide particles increases when increasing the filler amount, and this significantly reduces the tensile strength. It has also been noted that void creation in samples may generate this kind of behavior in filler-matrix systems; where voids and particle clustering were identified, a significant degree of plastic deformation was discovered as well [ 66 , 92 ]. From the characteristics witnessed from the graphs, it can be concluded that a tensile strength involving silica dioxide only would lead to a lower maximum tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…The agglomeration of silica dioxide particles increases when increasing the filler amount, and this significantly reduces the tensile strength. It has also been noted that void creation in samples may generate this kind of behavior in filler-matrix systems; where voids and particle clustering were identified, a significant degree of plastic deformation was discovered as well [ 66 , 92 ]. From the characteristics witnessed from the graphs, it can be concluded that a tensile strength involving silica dioxide only would lead to a lower maximum tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the dimensions of the additively manufactured parts correspond as closely as possible to the model produced in CAD. Compared to pure nylon, onyx is approximately 3.5 times more resistant, has a higher hardness and an HDT (Heat Deflection Temperature) of 140 °C [ 29 ]. Carbon fibres are supplied in the form of a continuous strand of about 1000 fibres with a diameter of 10 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The specimens were printed with a Mark Two (Markforged, Watertown, MA, USA), which uses fused filament fabrication technology to fabricate parts and is equipped with two nozzles to deposit independently matrix or fibre. For the matrix, we used Onyx, a nylon matrix reinforced with micro carbon fibres [19]. Furthermore, Kevlar was used as the reinforcement.…”
Section: Samples Productionmentioning
confidence: 99%
“…Over the years, it has assisted the rising of Additive Manufacturing (AM) techniques and the possibility of producing composite materials reinforced with continuous fibers that improve the mechanical properties of the printed parts. The most performing technique for realizing these materials is Fused Filament Fabrication (FFF) [18,19]. The most characteristic advantages of AM technique are freedom design and a high level of material customization that can be applied to every single layer that composes the printed part, making it lawful to investigate the geometric effect on bolted joints realized with this method [20,21].…”
Section: Introductionmentioning
confidence: 99%